Right to Life of a Child in India: An Overview (Medico Legal Update, 2021)
It would not be an exaggeration of words if it is said that children are the future of a nation. They are therepresentatives of the older generation in the upcoming world. They are filled with innocence and theirinnocence should be nurtured so as to make it persistent and to make the society free of corruption. Theirlevel of curiosity is very high and if it is preserved and explored then every child may become a researchoriented scientist, doctor, engineer or likewise. The most prominent international instrument through whichthe child right has got recognition is the Convention on Rights of Child, 1989. India being a signatory to itis complying with the standards laid down in it.